China's Provincial Growth Dynamics - Aziz, Jahangir; Duenwald, Christoph (Washington, D.C. : International Monetary Fund, 2001)
China's rapid overall growth since 1978 masks significant differences in relative economic performance across its provinces. This paper finds that, while per capita income of poor provinces are catching up with those in the rich, the relative income distribution appears to be stratifying into a bimodal distribution--the costal provinces grativating toward one mode, and the remaining provinces toward the other--with economic structure and policies playing important roles in the growth dynamics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Income; Per Capita Income; Process; WP; China, People's Republic of